Sino‐Nasal Outcome Test‐22: translation, cultural adaptation and validation in Portugal. (February 2016) - de Vilhena, D.; Duarte, D.; Lopes, G.
Abstract : Objectives: Sino‐Nasal Outcome Test‐22 is a questionnaire that evaluates the specific quality of life in chronic rhinosinusitis and was widely used in scientific literature. The aim of our study was to translate and culturally adapt Sino‐Nasal Outcome Test‐22 for the Portuguese reality and validate the version obtained for use in Portugal. Design: We translate Sino‐Nasal Outcome Test‐22 into European Portuguese according to the methodology recommended by the scientific literature. After translation, we proceeded with the evaluation of the questionnaire regarding its feasibility, reliability (internal consistency and test–retest reproducibility) and discriminant validity. Statistical analysis was performed usingspss 22.0. Setting: Patients treated at a single institute. Participants: We applied Sino‐Nasal Outcome Test‐22 questionnaire to 15 volunteers with no nasal or sinus disease and to 50 patients with chronic rhinosinusitis. Main outcome measures: Feasibility, reliability (internal consistency and test–retest reproducibility) and discriminant validity. Results: We observed good internal consistency, with general Cronbach's α coefficient of 0.935, good test–retest reproducibility (32.5 versus 32, P < 0.001), with Pearson coefficient of 0.99 ( P < 0.001) and Cohen Kappa coefficient of 0.898. The discriminant validity of the Portuguese version of Sino‐Nasal Outcome Test‐22 was confirmed by applying the Mann–Whitney U ‐test ( P < 0.001). Conclusions: Until now, there were no validated questionnaires to evaluate quality of life in patients with chronic rhinosinusitis in Portugal. Translation and validation of Sino‐Nasal Outcome Test‐22 in Portugal will allow a more consistent assessment of the specific quality of life of these patients and the comparison with international data. Thus, we recommend this version for use with the Portuguese population with chronic rhinosinusitis.